The evaluation of adult and community education and training programmes for offenders in Limpopo Province - Mathebula, Nkarhi Excellent (My University, 2020)
This study was about evaluating Adult and Community Education and Training programmes for offenders in Limpopo Province and its objective was to develop a model for best future practice for offenders. The study used a qualitative approach, which is embedded within the interpretive paradigm. A case study design was employed because of its ability to place a priority on people’s lived experience and the meanings they ascribe to their experiences. A total of 15 participants (six Educators, six Learners, and three Centre Managers) were identified through purposeful sampling. These 15 participants were recruited from Polokwane, Makhado, and Thohoyandou Correctional Centres in the Limpopo Province, South Africa. The study used document reviews, observations, semi-structured interviews and focus groups or mini-conference as instruments for data collection. The data collected was analysed using thematic analysis where the flow model of qualitative data analysis was employed. The study came up with two findings: in the first instance, Adult and Community Education and Training programmes for offenders are poorly funded. In the second instance proper need analysis is not conducted prior the implementation of programmes. Before embarking on the study, the researcher was of the view that education programmes for offenders are delivered in ways similar to mainstream education. In the third instance, educators do not receive training necessary for the teaching of offenders. Lastly, the relevant department does not adequately monitor the programme. The study offers turnaround strategies for future implementation of Adult and Community Education and Training programmes for offenders in Limpopo Province. The study has also developed a model to guide the future best practice of Adult and Community Education and Training programmes for offenders in Limpopo Province. The findings of the study have the following implications: firstly for policy makers: policies on funding of the programmes and training of educators should be developed. Secondly for practitioners: practitioners should conduct an effective compelling needs assessment so that relevant programmes can be designed. Furthermore, practitioners should ensure that there is ongoing monitoring of the programme in order to check its effectiveness. Thirdly, researchers should conduct further research into the factors that contribute to the success/failure of Adult and Community Education and Training programmes for offenders is recommended. It should be mentioned in conclusion that the programme can bring about better results should the above findings of the research be addressed by relevant stake holders. It is recommended that a more powerful research tool be used in order to go deeper into factors that contribute to the success or /failure of ACET programmes for offenders.
Thesis (Ph.D. (Educational Studies)) -- University of Limpopo, 2020
Keywords: Criminals; Offenders; Adult education; Adult learning; Community education; Adult learning -- South Africa; Criminals -- South Africa -- Limpopo; Adult education -- Evaluation; Community education -- South Africa -- Limpopo